Retirement 101 [compact disc, unabridged] : from 401(k) plans and social security benefits to asset management and medical insurance, your complete guide to preparing for the future you want - Cagan, Michele (Simon & Schuster, 2025)
Provides essential guidance on planning for retirement, whether you₂re just starting to save or nearing retirement age. With evolving structures like social security, Medicare, and investment accounts, staying informed is crucial. This updated edition includes the latest information on topics such as contribution limits, required minimum distributions, student debt payments, and enrollment changes. Covering everything from savings strategies and investment planning to choosing the best retirement location and calculating benefits, this book helps you develop a retirement plan tailored to your goals, whether you aim to retire early or continue working in some capacity.